2019
DOI: 10.1177/2319714519845770
|View full text |Cite
|
Sign up to set email alerts
|

Glass Ceiling for Women and Work Engagement: The Moderating Effect of Marital Status

Abstract: Women face several obstacles and barriers in order to attain high managerial positions as compared to men. They struggle to get fair representation in corporate boards and higher management levels. This is known as ‘glass ceiling’. The present study aims to explore the level of glass ceiling for women (GCW) in terms of its three major barriers, that is, personal barriers, organizational barriers and societal barriers among women managers working in the Indian service sector and identify the impact of GCW on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Therefore, after Covid-19 among flexible workers marital status stands out as a significant variable. It has been seen that married and single women (either widow or divorced) faced more impediments in their career progress [ 84 ].…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Therefore, after Covid-19 among flexible workers marital status stands out as a significant variable. It has been seen that married and single women (either widow or divorced) faced more impediments in their career progress [ 84 ].…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Although some invisible barriers to succes slowly begin to unravel. Sharma and Kaur (2019) found that marital status act as a moderator between organizational and societal barriers of glass ceiling women and their work engagement level, as Jackson (2001) opined family life also acts as a barrier since women give more preference to their family as compared to their career. In addition, according to Jain and Mukhreji (2010), Psychological factors prevent the progression of women to the leadership levels, besides other barriers such.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…In this sense, the idolisation of CEOs can further reinforce the inequality between men and women, making it even more challenging for women to climb the corporate ladder. The gendered perspective of CEOs can also be explained by the idea of the glass ceiling effect, which concerns the barriers that prevent women from climbing the career ladder (Sharma & Kaur, 2019). Meanwhile, Rhodes and Bloom (2018) also discuss how the idolisation of CEOs has resulted in exaggerated perceptions of their influence on the whole firm's performance.…”
Section: The Power Dynamics Proposed By French and Ravenmentioning
confidence: 99%